Analisis Tegangan pada Belokan Pipa Marine Boil Off Gas (MaBOG) Berbasis Metode Elemen Hingga - Rudi Kurniawan; Arhami Arhami; Rahmatsyah Maksum Ramsi (Jurnal Teknik Mesin Unsyiah, 2018)
This paper discusses the stress analysis of marine boil off gas pipe elbow. The piping system receives several loading conditions such as expansion load, occasional load, operation load, and sustain load, which are referred to as static loading conditions. As a result of the load conditions can be known stress distribution and examine the strength of the weld connection on the pipe elbow. The purpose of this research is to know the distribution of stress at the elbow of the pipe due to static loading conditions. The method used in this study using finite element analysis. The result of stress simulation in pipe elbow is 771 Pa and the result of calculation of stress in pipe elbow is 3,94 Pa. The result of piping system simulation shows the value of the pipe elbow e due to the load operation of 23151,34 kPa, the sustain load is 24918,91 kPa, the occasional load is 59110,83 and the expansion load does not produce the stress value. From the results of the analysis, the stress due to operating, sustain, and expansion loads are categorized as safe because they do not exceed the allowable stress values of each loading condition.